The answer to your problem is 17
Evaluate abs(2 x - 7) - 3 where x = 2:abs(2 x - 7) - 3 = abs(2 2 - 7) - 3
2×2 = 4:abs(4 - 7) - 3
4 - 7 = -3:abs(-3) - 3
Since -3<=0, then abs(-3) = 3:3 - 3
3 - 3 = 0:Answer: 0
Answer:
23
Step-by-step explanation:
-26-(-49)=-26+49=23
Answer:
it it two
Step-by-step explanation:
Answer: The price for the computer = $1152
Step-by-step explanation:
Let the first boy = F
Let the second boy = S
Let the price of computer = C
The second boy had 5/ 6 of the money the first had. I.e
S = 5/6 F
Then F = 6/5S ......(1)
The first boy had 7 /8 of the price of the computer. That is
F = 7/8C ....... (2)
Substitute F in (1) into (2)
6/5S = 7/8C
S = 5/6 × 7/8C
S = 35/48C ......(3)
Together they had $696.00 more than they need to pay. That is
F + S = C + 696 ........ (4)
Substitute equation 2 and 3 into 4
7/8C + 35/48C = C + 696
0.875C + 0.729C = C + 696
0.604C = 696
C = 696/0.604
C = 1152 dollars
Therefore, the price for the computer = $1152